The Late Roman Amphora workshops of Paros island in the Aegean Sea: Recent results - Diamanti, Charikleia (Rei Cretariae Romanae Fautorum Acta, 2017)
Paros is the third largest island of the Cyclades at the centre of the Aegean Sea. An episcopal seat already by the 4th century, it also belonged to the Provincia Insularum and in the Justinianic years to the quaestura justiniani exercitus. The comparatively little information for the history of Late Roman Paros can be enriched by the study of the pottery. In this paper are presented two Parian Late Roman Amphora kilns which add another important production centre to the historical map of the Aegean commercial network of that period.